A Roman altar on Mount Gerizim: Rediscovering a civic icon on tetradrachms of Neapolis (Samaria). Issue 1 (June 2021) - Kropp, Andreas J. M.
Abstract: This article examines the iconography of a type of Caracalla tetradrachm that has been newly attributed to Neapolis in Roman Palestine and whose reverse depicts a monumental altar decorated with statues of Tyche, Ephesian Artemis, and Kore Persephone. The study contextualizes these deities in the religious life of Neapolis and identifies the monument as an altar often depicted as a miniscule element in panoramic views of Mount Gerizim on the bronze coins of Neapolis. The tetradrachms provide, for the first time, a close-up view of this long-lost civic monument.